DAMPAK JOB STRESS DAN JOB SATISFACTION TERHADAP PSYCHOLOGICAL WELL-BEING PADA KARYAWAN PTS KOTA MEDAN - Sulaiman, Jihan; Sulaiman, Fahmi; Gusria, Amarisma (Smart Education, 2025)
Abstract: This study aims to determine the impact of job stress and job satisfaction on psychological well-being among employees of private universities in Medan. The population in this study consisted of 3,000 employees of private universities in Medan. The sample was selected using purposive sampling, where the population was selected based on specific criteria and using the Slovin formula, resulting in a sample size of 352 employees of PTS City of Medan. The study employed a quantitative approach. The instruments used were validated and reliable questionnaires on Job Stress, Job Satisfaction, and Psychological Well-Being. This study was analyzed using multiple regression analysis. The results of the study indicate that: (1) There is an impact of Job Stress and Job Satisfaction on Psychological Well-Being with F calculated = 168.053 > F table value = 3.02 with a significance value of 0.000 (p< 0.05) (2) There is a negative and significant impact of Job Stress on Psychological Well-Being with a calculated T value of -4.071 > T table = 1.967, and a significance level of 0.000 (p<0.05) (3) There is a positive and significant impact of Job Satisfaction on Psychological Well-Being with a calculated T value of 3.982 > T table = 1.967, and a significance level of 0.000 (p<0.05).Keyword: Job Stress, Job Satisfaction, Psychological Well-BeingAbstrak: Penelitian ini bertujuan untuk mengetahui dampak Job Stress dan Job Satisfaction Terhadap Psychological Well-Being Pada Karyawan PTS Kota Medan. Populasi dalam penelitian ini adalah 3000 Karyawan PTS Kota Medan. Pengambilan sampel dalam penelitian ini dengan teknik total sampling, dimana seluruh populasi akan menjadi sampel, sehingga jumlah sampelnya adalah 35 Karyawan PTS Kota Medan. Penelitian menggunakan pendekatan kuantitatif. Instumen yang digunakan adalah angket Job Stress dan Job Satisfaction dan Psychological Well-Being yang telah valid dan reliabel. Penelitian ini dianalisis dengan uji analisi regresi berganda. Hasil penelitian menunjukkan bahwa: (1) Ada dampak Job Stress dan Job Satisfaction terhadap Psychological Well-Being dengan F hitung= 168.053 > nilai F tabel = 3.02 dengan nilai signifikansi 0.000 (p< 0.05) (2) Ada dampak negatif dan signifikan Job Stress terhadap Psychological Well-Being dengan nilai T hitung= -4.071 > T tabel = 1,967, dan tarag signifikansi 0.000 (p<0.05) (3) Ada dampak positif dan signifikan Job Satisfaction terhadap Psychological Well-Being dengan nilai T hitung= 3.982 > T tabel = 1,967, dan taraf signifikansi 0.000 (p<0.05).Kata kunci: Job Stress, Job Satisfaction, Psychological Well-Being